Models and methods in transport logistics: status and prospects (Journal of Economic Research & Business Administration, 2016)
The article deals methods of the model used for the analysis of logistics processes. Such as transportation, which is a key function of the logistics associated with the movement of material resources, work in process, finished goods in vehicles on a particular technology. Transportation, in addition to the movement of goods, including logistics operations such as forwarding, materials handling, packaging, customs clearance, insurance risks. The article begins with an analysis of the simplest models, reducible to the transportation problem. Optimization models of homogeneous production in view of cargo flows on condition of linear dependence of the performance plan of production and transport can be based on open transport problem of linear programming. Further considers manufacturing, production, and transport patterns in «discrete and continuous» setting. Input a word in the article discrete manufacturing model and a description of how the economic process in the form of alternative options for the development of production facilities, from the set that you want to select the best set that satisfies the given constraints.
Keywords: models; methods; route; modification; the concept of «just in time»; the cost method.